(untitled) (Research, Society and Development, 2024)
Introduction: The aging population in Brazil has been occurring rapidly. Therefore, a deep reflection on social interaction and the quality of life of elderly people is essential. Objectives: To identify the sociodemographic, family, and health characteristics of elderly people and correlate positive social interaction with quality of life domains. Methodology: A quantitative, descriptive, analytical, and cross-sectional study. The study included 301 elderly people living in a city in southern Minas Gerais. The inclusion criterion was elderly individuals with preserved cognitive ability, assessed by a mental evaluation questionnaire. The exclusion criterion was elderly people with compromised clinical signs. Descriptive statistics were used for data analysis, with frequency and percentage applied to qualitative or categorical variables. Pearson’s correlation coefficient was used for correlations. A 5% error was adopted for statistical significance with a 95% confidence level. Results: Regarding the sociodemographic, family, and health characteristics of the elderly: 45.18% were between 70-79 years old, 54.16% were male, 64.11% received 1 to 2 minimum wages, 73.76% did not report falls in the last month, 69.77% used polypharmacy, and 52.83% had comorbidities. As for Pearson’s linear correlation, a p-value of < 0.001 was obtained for positive social interaction versus quality of life in all domains. Conclusion: It is evident that elderly people who have established positive social interaction consequently show better quality of life in all domains.